Team Sky's innovation hub - Hill, G. (Sports Performance & Tech, 2016)
Dr. Scott Drawer is currently leading a new project with TeamSky and Sky to investigate the development of unique concept around the exploration of human potential through sport and other creative domains. Prior to this, he led a team of science and medicine staff across the player development pathway for England Rugby. His career started within the GB Olympic and Paralympic system - developing and leading the Research & Innovation programme across 5 summer and winter Olympic and Paralympic Games. We spoke to him about his work at Team Sky, his career and the changing face of sports analytics and innovation.